Improving Anesthesia Safety in Low-resource Settings. Issue 1 (March 2019) - Khan, F.A.; Merry, A.F.
Abstract : ( Anesth Analg . 2018;126(4):1312–1320) Over the last century, anesthesia safety has improved significantly in high-income countries (HICs) of the world but has not done the same in low-income countries (LICs), due to characteristics like poor infrastructure and shortages of anesthesia providers, essential drugs, equipment and supplies. In the present article, the authors argued that further disregard of this global anesthesia crisis could result in failure to achieve the full potential of LIC populations. In order to address this issue, the authors provided a high-level overview of some of the relevant challenges and discussed current and potential initiatives at global, regional, national, and local levels. The authors believe that understanding how such systems work is essential to achieving sustainable, widespread improvement globally for safety in anesthesia.